Hidbokas: Pemanfaatan Botol Bekas Sebagai Media Tanam Hidroponik pada PKH Desa Ngadirejo Magetan - Aji, Krisna Robitara; Murseto, Taufik Dian; Hafidz, Feisal; Kinaldhi, Te’o; Gutomo, Rahmat; Pratiwi, Dian (Universitas Merdeka Madiun, 2018)
Hydroponic training activities were held in the village of Ngadirejo Magetan. Activity participants were PKH members in the village. PKH (Program Keluarga Harapan) or in international is similar with Conditional Cash Transfers (CCT) is a program from government to help poor families .All participants were enthusiastic in participating in the training. Armed with hydroponic cultivation skills, it is expected that the community can use plastic bottle waste for planting media. in addition, this activity can also generate income for the community, especially housewives.